An outline of strategies for building an innovation system for Knowledge City - Crane, Keith, 1953-; Shatz, Howard J.; Nataraj, Shanthi; Popper, Steven W., 1953-; Wang, Xiao.; Rand eBooks (Santa Monica, CA : RAND, 2012)
China$1 (Bs Guangzhou Development District (GDD) will be the site of the new innovation cluster known as Sino-Singapore Guangzhou Knowledge City. Jointly developed by GDD and Singbridge of Singapore, Knowledge City will be an environmentally and technologically advanced city that hosts innovative industries and their associated knowledge workers. To achieve this goal, GDD must design a strategic plan to pursue three primary goals: to attract high-tech companies and enable their growth, to attract and retain a highly skilled, innovative workforce, and to ensure the availability of innovation-oriented financing. This report serves as an outline of a set of strategies for Knowledge City and is intended to help GDD create conditions that are conducive to innovation and the commercialization of new technologies. To this end, it assesses the challenges that GDD will face, recommends policies to address these challenges, and proposes a coordinated set of actions to implement these policies in a way that meets Knowledge City$1 (Bs goals. It also offers a general timetable and priority ranking for the policies and actions to help ensure that Knowledge City is able to attract top talent and provide a growth-oriented environment for innovative businesses and research institutions. This is a companion volume to another RAND report, Creating an Innovation System for Knowledge City (TR-1293-GDD), which presents results from the interim analyses and supporting evidence for the study$1 (Bs conclusions.s
Introduction -- Attracting High-Technology Companies and Enabling Their Growth -- Attracting and Retaining People -- Financing -- Priorities, Ease of Implementation, and Sequencing -- Indicators of Innovation.
"A RAND Infrastructure, Safety, and Environment Program."
"RAND Environment, Energy, and Economic Development."
Includes bibliographical references (p. 69-72).
Also available on the internet via WWW in PDF format.
Keywords: City planning -- China -- Guangzhou; High technology industries -- China -- Guangzhou; Knowledge workers -- China -- Guangzhou; Sustainable urban development -- China -- Guangzhou; Technological innovations -- China -- Guangzhou; Guangzhou (China) -- Economic conditions; Electronic books